PERAN MANAJEMEN PD â€œPASAR SURYAâ€ DALAM MENINGKATKAN KONTRIBUSI PENDAPATAN ASLI DAERAH (PAD) KOTA SURABAYA (Studi Kasus pada PD Pasar Surya Pasar Rungkut Baru) - Nurliana, Mila (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Management of PD Pasar Surya Pasar Baru Rungkut still lacking even impressed neglected, therefore we need a change in the management of PD Pasar Surya Pasar Baru Rungkut to play a more in increasing its contribution to revenue (PAD) in Surabaya. The purpose of this study was to determine and describe the role of the management of PD Pasar Surya Pasar Baru Rungkut in Increasing Revenue (PAD) in Surabaya. This study was a qualitative research. Informants in this study consists of the management and managers Rungkut Pasar Baru, New Rungkut market traders and parking attendants in Rungkut Pasar Baru. Data were analyzed with descriptive qualitative data analysis techniques. The results showed that the management role of PD Pasar Surya Pasar Baru Rungkut in increasing contributions to revenue (PAD) in Surabaya is on the management booths of the existing market. Their booths empty marketplace utilized leased to the merchant market which are located adjacent to the PD Pasar Surya Rungkut Pasar Baru as a warehouse for the number of booths that there is more than the number of traders in Pasar Surya PD Pasar Baru Rungkut. This fact has provided additional income and budget for PD Pasar Surya Pasar Baru Rungkut so as to contribute also on enhancements to revenue (PAD) in Surabaya. Suggestions can be submitted related to the study are PD Pasar Surya Pasar Rungkut Baru supposed to promote and encourage street vendors (PKL) or to traders who do not have a location to sell fixed in the District Rungkut to rent booths PD Pasar Surya Pasar Rungkut Baru in conduct trading activities. Keywords: Role Management, Local Revenue (PAD), Regional Companies Market